(untitled) (Research, Society and Development, 2020)
The present work aims to elaborate a cookie type cookie with the addition of red rice residue flour (FRAV) and to evaluate its storage instrumental texture and water activity during 60 days. The residue used was obtained in the extraction of red rice starch and was dehydrated at 50 °C for 8h. The cookies were made in 3 formulations (0, 50 and 100%) of FRAV. The texture (firmness and fracturability) and water activity parameters were evaluated periodically with intervals between measurements of 15 days totaling 60 days of storage. The biscuit formulation (F3) with 100% flour from the red rice residue showed higher firmness and fracturability, however, during 60 days of storage it was noticeable significant differences of these parameters due to increased water activity in the same time period. Therefore, the elaboration of the cookie becomes viable to reduce food expenses and minimize the environmental impacts of the country.